(E)-5-Phenyl-N-(2-thienylmethylene)-1,3,4-thiadiazole-2-amine - Demirtas, Gunes; Dege, Necmi; Sekerci, Memet; Servi, Sueleyman; Dincer, Muharrem (Int Union Crystallography, 2009)
In the title compound, C13H9N3S2, the thiophene and phenyl rings are oriented at dihedral angles of 8.00 (7) and 6.31 (7)degrees, respectively, with respect to the central thiadiazole ring. No significant C-H center dot center dot center dot S and pi-pi interactions exist in the crystal structure.